Subordinasi Norma Pidana Lingkungan dalam Penegakan Hukum terhadap Tambak Udang Ilegal Berdasarkan Teori Sistem Hukum Friedman - Rahma, Laela Novitri Ervia; Rifqi, Muhammad Raikhan Nur (LPPM Universitas Muria Kudus, 2025)
Environmental criminal law enforcement in Indonesia faces structural challenges due to the normative subordination between Law No. 32 of 2009 on Environmental Protection and Management and Law No. 5 of 1990 on Conservation. This study aims to analyze the effectiveness of environmental criminal norms in judicial practice and their implications for ecological protection. The method employed is normative legal research using a juridical-normative approach, with primary and secondary legal materials and descriptive qualitative analysis. Results indicate that legal authorities tend to apply administrative conservation norms, overlooking scientific evidence and the potential application of Article 98 of Law No. 32/2009, preventing optimal operationalization of environmental criminal law. The novelty of this study lies in mapping normative subordination as a structural factor hindering substantive ecological protection. Reforming norm hierarchies, strengthening institutional capacity, and changing legal culture are necessary to make environmental criminal law the primary instrument of ecological protection.